2019
DOI: 10.48550/arxiv.1911.09738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rethinking Normalization and Elimination Singularity in Neural Networks

Siyuan Qiao,
Huiyu Wang,
Chenxi Liu
et al.

Abstract: In this paper, we study normalization methods for neural networks from the perspective of elimination singularity. Elimination singularities correspond to the points on the training trajectory where neurons become consistently deactivated. They cause degenerate manifolds in the loss landscape which will slow down training and harm model performances. We show that channel-based normalizations (e.g. Layer Normalization and Group Normalization) are unable to guarantee a far distance from elimination singularities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Huang et al showed that CWN combined with BN can improve the original networks with only BN. The idea of combining normalizing weights and activations to improve performance has been widely studied [24], [52], [141], [171]. Moreover, Luo et al proposed cosine normalization [172], which merges layer normalization and weight normalization together.…”
Section: Combining Activation Normalizationmentioning
confidence: 99%
“…Huang et al showed that CWN combined with BN can improve the original networks with only BN. The idea of combining normalizing weights and activations to improve performance has been widely studied [24], [52], [141], [171]. Moreover, Luo et al proposed cosine normalization [172], which merges layer normalization and weight normalization together.…”
Section: Combining Activation Normalizationmentioning
confidence: 99%
“…DeepLabv3+ is composed of an encoder network and decoder network; in the first version, we change the decoder by replacing all the convolutions with our new version of LP-BNN convolutions and leave the encoder unchanged. In the second variant we use weight standardization [42] on the convolutional layers of the decoder, replacing batch normalization [22] in the decoder with group normalization [52]. We denote the first version LP-BNN and the second one LP-BNN + GN.…”
Section: Semantic Segmentationmentioning
confidence: 99%
“…Du et al (2018) showed that for GD over one-hidden-layer weight normalized CNN, with a constant probability over initialization, iterates converge to global minima. Qiao et al (2019) compared different normalization techniques from the perspective of whether they lead to points, where neurons are consistently deactivated. Wu et al (2019) established the inductive bias of gradient flow with weight normalization for overparameterized least squares and showed that for a wider range of initializations as compared to normal parameterization, it converges to the minimum L 2 norm solution.…”
Section: Related Workmentioning
confidence: 99%